Effect of Exercise on Breast Cancer–Related Lymphedema: What the Lymphatic Surgeon Needs to Know - Panchik, Daniel; Masco, Sarah; Zinnikas, Patrice; Hillriegel, Brooke; Lauder, Tori; Suttmann, Erica; Chinchilli, Vernon; McBeth, Maureen; Hermann, William (Journal of Reconstructive Microsurgery, 2019)
Background Breast cancer–related lymphedema (BCRL) affects many areas of daily living. Individuals with lymphedema may experience chronic and progressive swelling, recurrent skin infections, and decreased self-image and quality of life. For many years, it was considered best practice for this population to avoid exercise; however, in recent years, research has begun to challenge this belief. This systematic review and meta-analyses examined the recent literature on the effects of exercise for patients with, or at risk for, BCRL to inform best practice.Methods A total of 807 articles were retrieved from CINAHL, Academic Search Complete, Medline, and PubMed. Results were systematically filtered to 26 articles through inclusion criteria, exclusion criteria, and the Effective Public Health Practice Project quality assessment tool for quantitative studies. Data were pooled from studies containing relative and absolute volume measurements of limb volume, as well as upper extremity function measured by the Disabilities of Arm, Shoulder, and Hand (DASH) questionnaire; meta-analyses were conducted using SAS software.Results The literature was reviewed and statistically analyzed. Results have indicated aerobic exercise, resistance exercise, stretching, yoga, qigong, and pilates can be safe and effective in the management of symptoms for those with, or at risk for, BCRL.Conclusion Several forms of exercise appear to be safe interventions for clinicians to use when treating this population and offer benefits such as improved quality of life, strength, body mass index, and mental health and decreased pain and lymphatic swelling. Additional research should be conducted to further examine the efficacy and safety of nontraditional forms of exercise in the treatment of BCRL.
Keywords: breast cancer–related lymphedema; exercise; arm lymphedema; breast cancer